Neuropeptide Y at the cellular level – Studies on PreproNPY L7P Polymorphism and the Mitochondrial Form of NPY - Kaipio, Katja (fi=Turun yliopisto|en=University of Turku|, 2009)
Neuropeptide Y (NPY) is a widely expressed neurotransmitter in the central and peripheral nervous systems. Thymidine 1128 to cytocine substitution in the signal sequence of the preproNPY results in a single amino acid change where leucine is changed to proline. This L7P change leads to a conformational change of the signal sequence which can have an effect on the intracellular processing of NPY. The L7P polymorphism was originally associated with higher total and LDL cholesterol levels in obese subjects. It has also been associated with several other physiological and pathophysiological responses such as atherosclerosis and T2 diabetes. However, the changes on the cellular level due to the preproNPY signal sequence L7P polymorphism were not known. The aims of the current thesis were to study the effects of the [p.L7]+[p.L7] and the [p.L7]+[p.P7] genotypes in primary cultured and genotyped human umbilical vein endothelial cells (HUVEC), in neuroblastoma (SK-N-BE(2)) cells and in fibroblast (CHO-K1) cells. Also, the putative effects of the L7P polymorphism on proliferation, apoptosis and LDL and nitric oxide metabolism were investigated. In the course of the studies a fragment of NPY targeted to mitochondria was found. With the putative mitochondrial NPY fragment the aim was to study the translational preferences and the mobility of the protein. The intracellular distribution of NPY between the [p.L7]+[p.L7] and the [p.L7]+[p.P7] genotypes was found to be different. NPY immunoreactivity was prominent in the [p.L7]+[p.P7] cells while the proNPY immunoreactivity was prominent in the [p.L7]+[p.L7] genotype cells. In the proliferation experiments there was a difference in the [p.L7]+[p.L7] genotype cells between early and late passage (aged) cells; the proliferation was raised in the aged cells. NPY increased the growth of the cells with the [p.L7]+[p.P7] genotype. Apoptosis did not seem to differ between the genotypes, but in the aged cells with the [p.L7]+[p.L7] genotype, LDL uptake was found to be elevated. Furthermore, the genotype seemed to have a strong effect on the nitric oxide metabolism. The results indicated that the mobility of NPY protein inside the cells was increased within the P7 containing constructs. The existence of the mitochondria targeted NPY fragment was verified, and translational preferences were proved to be due to the origin of the cells. Cell of neuronal origin preferred the translation of mature NPY (NPY1-36) when compared to the non neuronal cells that translated both, NPY and the mitochondrial fragment of NPY. The mobility of the mitochondrial fragment was found to be minimal. The functionality of the mitochondrial NPY fragment remains to be investigated. L7P polymorphism in the preproNPY causes a series of intracellular changes. These changes may contribute to the state of cellular senescence, vascular tone and lead to endothelial dysfunction and even to increased susceptibility to diseases, like atherosclerosis and T2 diabetes.